2009
DOI: 10.22146/gamaijb.5521
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Government Debt Issuance on Short-Term interest rates in Indonesia

Abstract: This paper analyzes whether the expansionary fiscal policy funded by issuing debt instruments in financial markets will increase short-term interest rates. If  the expansionary fiscal policy increases interest rates, which decrease private spending especially investment, crowding out occurs. This is interesting because global economic crisis has encouraged many countries to run large budget deficits to stimulate the economy. Indonesia has also run budget deficit during this crisis and even in years before. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In other words, uncertainty in the future when the debt must be repaid is transformed into higher risk in the prices level. Eventually, the behavior of terms of trade tends to decline in the long-run, as found by Abimanyu (1998) in the case of the budget deficit to exchange rates and Adiningsih (2009) in the case of a government bond to interest rates relationships respectively. Furthermore, looking at the control variable, the estimated coefficient of the government size is statistically significant.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In other words, uncertainty in the future when the debt must be repaid is transformed into higher risk in the prices level. Eventually, the behavior of terms of trade tends to decline in the long-run, as found by Abimanyu (1998) in the case of the budget deficit to exchange rates and Adiningsih (2009) in the case of a government bond to interest rates relationships respectively. Furthermore, looking at the control variable, the estimated coefficient of the government size is statistically significant.…”
Section: Resultsmentioning
confidence: 92%
“…Other previous studies have been characterized by the inward-oriented types. They focused on the impact of fiscal policy partially on the inflation rate (Snyder, 1985;Kuncoro, 2015), exchange rate (Abimanyu, 1998), and interest rates (Adiningsih, 2009). Recently, Simorangkir and Adamanti (2010) analyzed the economic impact of fiscal stimulus, Basri and Rahardja (2011) assessed the fiscal position, and Surjaningsih et al (2012) observed output and prices volatility in accordance with the global financial crisis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding private investment although the response line is in negative area but the confidence bands encompass the zero-line (Figure 3); therefore, the private investment response is not significant. Within this concept, Adiningsih (2009) using monthly data of 2000-2008 and ECM model claims that rising government debt increases interest rate, thus, crowds out private investment. The response of human capital is negligible as well.…”
Section: Resultsmentioning
confidence: 99%
“…Kwan (2007) obtained that private and government consumption are strong complements. Most of other works in Indonesia has been conducted separately in particular concentrated on the inflation rate (Snyder, 1985), private investment (Ikhsan & Basri, 1991), private consumption (Adji, 1995), current account (Adji, 1998), exchange rate (Abimanyu, 1998), tax revenue (Saleh, 2002), and interest rates (Adiningsih, 2009). In fact, there are mixed evidences of crowding-out and crowding-in effect.…”
Section: Literature Reviewmentioning
confidence: 99%